Efektivitas Penerapan Teknik Manajemen Waktu dalam Belajar Mandiri Matematika - Sari, Intan Permata; Siregar, Sakinah Ubudiyah; Hasibuan, Lily Rohanita (Jurnal Ragam Pengabdian, 2026)
This study aims to examine the effectiveness of applying time management techniques in self-directed mathematics learning. A quasi-experimental method with a pre-test and post-test control group design was employed. The subjects were 60 seventh-grade students of SMP Negeri 5 Bilah Barat, divided into an experimental group (n=30) receiving the Pomodoro technique intervention and a control group (n=30) engaging in conventional self-study. Data were collected through learning achievement tests, a time management habits questionnaire, and learning logs. Data analysis utilized descriptive statistics, prerequisite tests (normality and homogeneity), and an Independent Sample T-Test at a 5% significance level. Results revealed that the experimental group's post-test mean (84.17) was significantly higher than the control group's (72.30) with t = 6.971 and p = 0.000. The mean N-Gain of the experimental group was 0.62 (moderate category) and the control group 0.34 (moderate category), indicating a greater improvement in the experimental group. Most students (86.7%) fell into the high and very high categories in applying time management techniques. Thus, the application of time management techniques proved effective in improving mathematics learning outcomes in a self-directed learning context.